2023
DOI: 10.7759/cureus.38410
|View full text |Cite
|
Sign up to set email alerts
|

A Head-to-Head Comparison of Computed Tomography Colonography, Optical Colonoscopy, and Colon Endoscopic Capsule for the Detection of Polyps After Partial Colectomy or Rectosigmoidectomy for Colorectal Cancer: A Pilot Study

Abstract: Background and objective Optical colonoscopy is the gold standard method for the diagnosis of colorectal cancer (CRC) and it allows for biopsy and resection, as well as documentation of synchronous lesions. CT colonography (CTC) and colon endoscopic capsule (CEC) are also recommended as alternative minimally invasive or non-invasive procedures. Prospective studies comparing these three approaches are scarce in the current literature. In light of this, the aim of this pilot study was to compare the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A recent pilot study investigated the performance of CCE, CTC, and CC in 21 patients undergoing all three procedures in tandem [45]. The study showed that CC and CCE were comparable in terms of polyp detection, and both were superior to CTC.…”
Section: Non-invasive and Minimally Invasive Alternatives To Conventi...mentioning
confidence: 99%
“…A recent pilot study investigated the performance of CCE, CTC, and CC in 21 patients undergoing all three procedures in tandem [45]. The study showed that CC and CCE were comparable in terms of polyp detection, and both were superior to CTC.…”
Section: Non-invasive and Minimally Invasive Alternatives To Conventi...mentioning
confidence: 99%